2015
DOI: 10.1021/es504258u
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Biodegradation-Promoting Additives for Plastics

Abstract: Biodegradation-promoting additives for polymers are increasingly being used around the world with the claim that they effectively render commercial polymers biodegradable. However, there is a lot of uncertainty about their effectiveness in degrading polymers in different environments. In this study, we evaluated the effect of biodegradation-promoting additives on the biodegradation of polyethylene (PE) and polyethylene terephthalate (PET). Biodegradation was evaluated in compost, anaerobic digestion, and soil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
79
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(87 citation statements)
references
References 35 publications
6
79
0
2
Order By: Relevance
“…The authors concluded that no biodegradation was observed after the addition of the oxo-degradable additive in PE. Similar results were obtained by other research groups [201] studying the effect of biodegradation promoting additives on the biodegradation of PE and PET. In this study, no evidence was found that these additives promote and/or enhance biodegradation of polymers.…”
Section: Polymerssupporting
confidence: 90%
See 1 more Smart Citation
“…The authors concluded that no biodegradation was observed after the addition of the oxo-degradable additive in PE. Similar results were obtained by other research groups [201] studying the effect of biodegradation promoting additives on the biodegradation of PE and PET. In this study, no evidence was found that these additives promote and/or enhance biodegradation of polymers.…”
Section: Polymerssupporting
confidence: 90%
“…In this study, no evidence was found that these additives promote and/or enhance biodegradation of polymers. Therefore, the above results lead us to conclude on the need for further understanding about the effect of using biodegradation-promoting additives [201].…”
Section: Polymersmentioning
confidence: 82%
“…Earth's ecosystem is approaching a planetary-scale transformation as a result of human influence 1 . Nowadays, a wide variety of petroleum-based synthetic polymers are produced worldwide to the extent of 20-fold increase over the five decades since 1960s and a slowdown of this trend is not expected 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Several countries have begun to face the problem by implementing restrictive and regulatory laws regarding the production and use of plastics. New formulations of polymers have been proposed to obtain degradable materials whose final ecological and physical footprint is much smaller [1,2].…”
Section: Introductionmentioning
confidence: 99%